Answer:
3(2x - 5)(x + 2)
Step-by-step explanation:
6x^2 - 3x - 30
= 3(2x^2 - x - 10)
= 3(2x - 5)(x + 2) (answer).
(x−a)(x−b)
=(x+−a)(x+−b)
=(x)(x)+(x)(−b)+(−a)(x)+(−a)(−b)
=x2−bx−ax+ab
<h2><u><em>
=ab−ax−bx+x2</em></u></h2>
1280 Is the correct anwser
<h3>
Answer: Yes, it is a function</h3>
This is a function because there are no x values that repeat.
If we had repeated x values, then this would mean a certain input x leads to multiple outputs y, and that would not make it a function.
For instance, if we had (2,1) and (2,2) at the same time, then the input x = 2 leads to multiple outputs y = 1 and y = 2 at the same time. A function would not be possible in this example.
A function is only possible if any input x leads to exactly one output y. It is possible for y to repeat itself and still have a function.